2007
DOI: 10.1037/0012-1649.43.5.1216
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers monitor the relative accuracy of informants.

Abstract: In 2 studies, the sensitivity of 3- and 4-year-olds to the previous accuracy of informants was assessed. Children viewed films in which 2 informants labeled familiar objects with differential accuracy (across the 2 experiments, children were exposed to the following rates of accuracy by the more and less accurate informants, respectively: 100% vs. 0%, 100% vs. 25%, 75% vs. 0%, and 75% vs. 25%). Next, children watched films in which the same 2 informants provided conflicting novel labels for unfamiliar objects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
427
6
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(461 citation statements)
references
References 26 publications
26
427
6
2
Order By: Relevance
“…Were children who understood this more likely than those who did not to override their expectation about the target's identity and believe the speaker's contradicting suggestion? In previous research, no relationship has been found between children's false belief understanding and their preference for a previously accurate over a previously inaccurate speaker (Harris, 2007;Pasquini, Corriveau, Koenig, & Harris, 2007). However, in that research the inaccurate speaker misnamed familiar objects despite apparently having full information, so children had no independent evidence that the inaccuracy could be attributed to a false belief.…”
mentioning
confidence: 66%
“…Were children who understood this more likely than those who did not to override their expectation about the target's identity and believe the speaker's contradicting suggestion? In previous research, no relationship has been found between children's false belief understanding and their preference for a previously accurate over a previously inaccurate speaker (Harris, 2007;Pasquini, Corriveau, Koenig, & Harris, 2007). However, in that research the inaccurate speaker misnamed familiar objects despite apparently having full information, so children had no independent evidence that the inaccuracy could be attributed to a false belief.…”
mentioning
confidence: 66%
“…Previous research shows that even young children distinguish informants who provide false information from those who provide accurate information, and preferentially learn from previously accurate informants (Koenig, Clément, & Harris, 2004;Koenig & Harris, 2005;Jaswal & Neely, 2006;Pasquini, Corriveau, Koenig, & Harris, 2007;Birch, Vautier, & Bloom, 2008). For instance, preschoolers are more likely to accept a label for a novel object from an informant who previously labeled a familiar object correctly (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Four-year-olds understand that sometimes people do not have enough knowledge to provide accurate statements (Sodian, 1988;Wimmer & Perner, 1983), and that some people are more knowledgeable than others for a given topic (Lutz & Keil, 2002). Preschoolers discount information presented by a discredited source, such as an adult who was described as being "silly" (Lampinen & Smith, 1995), or someone that has made a series of mistakes in the past (Pasquini, Corriveau, Koenig, & Harris, 2007), and kindergartners discount implausible statements about transgressions that clearly contradict with reality (e.g., a ghost jumped out of a book and broke a glass; Lee, Cameron, Doucette, & Talwar, 2002).Thus, young children can recognize that someone can be a poor judge, and may be unable to provide a correct assessment. But what about in cases where it is less certain, but highly likely, that someone may show poor judgment?…”
mentioning
confidence: 99%